Relatos de práticas de ensino de leitura na Educação de Jovens e Adultos-EJA no município de Nova Andradina/MS - Souza, Ronyvaldo de (2020)
This thesis has as its theme exposure and reflection of reports of reading teaching practices in Youth and Adult Education - EJA in Nova Andradina / MS. It is situated in the research line “reading, teaching and writing of Portuguese Language” of the Pontifical Catholic University of São Paulo. It is theoretically based on the metacognitive and cognitive theories of reading structured in Kleiman (1998), Foucambert (1994), Solé (1998) Geraldi (1988, 1996, 1997) and the official documents of Brazilian education for youth and adult education. Methodologically, this is a qualitative and quantitative research based on specific graphics of the analyzed municipality and presents results that require the interpretation of the researcher. The results show that there is still a lack of public policies that dismantle old conceptions of what will be the function of EJA nationally and specifically in Andradina / MS. This is why this work is necessary as an instrument for reflection of the current condition on the proposed theme in thisresearchobject